A Model for National Human Rights Systems? New Governance and the Convention on the Rights of Persons with Disabilities. Issue 3 (3rd July 2019) - Lorion, Sébastien
ABSTRACT: The 2006 Convention on the Rights of Persons with Disabilities (CRPD) epitomises the institutional turn of the international human rights regime in two ways. It requests that States Parties conform to specific organisational features, and aims at transforming not only state behaviour, but also social norms of all actors in society, to anchor a human rights approach to disability. At the centre of this exercise lies CRPD Article 33 on 'National Implementation and Monitoring', which foresees that States Parties should establish or appoint focal points, coordination mechanisms and independent monitoring bodies. In addition, the principle of participation permeates the Convention. This article analyses attempts by norm entrepreneurs to design models for human rights systems based on the CRPD, and in particular the convergence of those models towards institutional arrangements inspired by new governance theories. Building upon a study of Article 33 scholarship, the article discusses the validity of such interpretations. It calls to carefully consider the implications of those new governance-oriented interpretations, notably how they challenge the role of courts and litigation, and potentially recasts the meaning of rights and responsibility. The article concludes on the need to better integrate different treaty compliance paths.